Studying the reality of sports activities programs in youth forums in Babil Governorate - Khamail Abdul Hussein Jawad (Mustansiriyah Journal of Sports Science, 2024)
The research problem is determined by explaining the reality of sports activity in youth and sports forums and what are the problems and obstacles facing managers, supervisors and coaches working in this institution during the course of their work, and highlighting the most important problems and obstacles facing the work of managers, supervisors and coaches working in youth and sports forums. The aim of the research is to : Statement of the cur-rent reality of sports activity included in the work program of youth and sports forums. Diagnosing the problems and obstacles facing the work of sports managers, supervisors, and sports coaches working in youth and sports forums. The most important conclusions are: The relative discrepancy in the answers of the research sample by explaining the true reality of the sports activity program. The researcher attributes the reason for this to the nature of the job held by each individual working in the youth and sports fo-rums and the amount of direct contact with the sports activity program in the forum. Despite the presence of regular stadiums and halls in youth and sports forums, they are not sufficient for their purpose, and most of them are not suitable for practicing sports activity, whether for training or competition. The reason for this is the lack of periodic and continuous maintenance and maintenance.